Spatio-temporal pattern of drought in Northeast of Iran - Akhtari R.; Bandarabadi S.R.; Saghafian B. (Drought management: scientific and technological innovations, 2008)
Drought events impose negative effects on the environment and can cause widespread non-structural damages. These damages are persistent in arid and semiarid areas. Iran, located in a generally arid region, has experienced severe droughts in the past decade. Recent studies have shown that droughts have frequently occurred in some or most parts of the country. In this paper, spatial characteristics of droughts were studied in the northeast of Iran based on Standard Precipitation Index (SPI) on the 12 months time scale. Then, severity-area-frequency curves were extracted by performing frequency analysis of the area under drought in the entire region. Furthermore, drought occurrence probability was plotted using TPSS interpolator which showed that a good portion of the area with 20% drought probability exists. Such map facilitates the prioritization of water resources planning in drought cases.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)